A Giant Borderline Phyllodes Tumor of Breast With Skin Ulceration Leading to Non-Insular Tumorigenic Hypoglycemia: A Case Report and Literature Review - Zhao, Jinlu; Gao, Meizhuo; Ren, Yi; Cao, Shaodong; Wang, He; Ge, Ruisheng (Frontiers in Endocrinology, 2021)
Phyllodes tumor (PT) is a special type of breast tumors, including three types: malignant, borderline, and benign. Most of these tumors form unilateral disease and can rapidly increase in size. The occurrence of axillary lymph node metastasis is rare. Tumor-associated hypoglycemia can be divided into non-islet cell tumor and insulinoma. In non-islet cell tumor hypoglycemia (NICTH), a considerable high molecular weight form of insulin like growth factor 2 (IGF-2) is formed, which abnormally binds to insulin receptors in the tissues and causes hypoglycemia. Breast phyllodes tumors with NICTH are rare and first reported in 1983. Surgical resection is the main treatment and hypoglycemia symptoms usually resolve after surgery. Nevertheless, prior to surgery, intravenous glucose infusion is used to maintain blood glucose levels. A female patient presented with a rapidly growing breast mass and was diagnosed with a phyllodes tumor with NICTH at our hospital in August 2020; she was successfully treated through surgical resection. We reviewed the relevant literature to investigate and analyze the relationship between NICTH and phyllodes tumors, as well as optimize its diagnosis and treatment.